Museus e centros culturais virtuais: uma análise sobre o nível de interação e mediação entre o sujeito e o conhecimento - Pierobon, Jorge Luiz (2014)
The purpose of this paper is to present the results of our research on virtual museums and cultural centers (MCCV), more specifically, about their interaction functions and mediation between the subject and the knowledge. We find it appropriate to discuss this issue for two basic reasons, namely, first, we live in a globalized society, connected by the Internet network, where all sorts of business, entertainment, communication and even educational activities are being transmitted and accessed by people all over the world. Second, we see great growth of so‐called educational sites where our attention focuses on MCCV. Thus, we aimed to answer the following questions: What level of interaction and mediation found in MCCV? The MCCV can really be classified as mediators between the subject and knowledge? Can we actually learn something from these MCCV? To answer such questions, we had to: identify and characterize MCCV , identify its origins , languages and settings in digital grafocêntricas constituent societies, analyzing the adopted technologies in teaching and learning. Analyze the theories of Vygotsky, Freire and others on subjects such as: interaction, mediation, learning, education, etc.. Finally, we evaluate the technical level navigation on the websites of MCCV as well as the level of interaction and mediation found these. Thus , present results and final conclusions , where we present an overview of the major points found in the search , and we believe that there is a good level of interaction and mediation in current MCCV , but that there is room for improvement, especially in question interaction, where forums and chats to exchange experiences and clarify doubts , which would have a greater attention to its developers, and also, there is a need for a greater number of tools to use visual deficintes as speakers and increased sources. This study, we are sure, will be useful to science in order to address a point still little studied in graduate programs in education major public universities in Brazil. And finally, we believe it is useful to society, in terms of provision of references for further study and clarification on this matter.